Kewajiban dan Hak Wanita Hindu Dalam Keluarga dan Masyarakat - I Nyoman Kiriana (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2017)
In the view of Hinduism, women have a glorious position that is worthy of respect and domicile almost equal to men. The difference between men and women lies in guna (skill) and karma (deeds). The obligations of women in Hindu families and society are as mothers, childbearing, hereditary, husband-lovers and can free the ancestors from their misery. A woman is entitled to a decent life in Hindu families and society and gained recognition of her existence so that her standing parallels men in both law and government.